Single step joint: overview of European standardized approaches and experimentations - Verbist, Maxime P. (2016)
In the field of the built heritage restoration, engineers have to work with old structures made of badly preserved timber elements. The assessment of timber elements and connections is a major issue for engineers involved in a restoration project. Before thinking about any intervention technics, engineers have to properly understand how the carpentry connections fail, which parameters influence the failure modes (geometry of the joint, mechanical properties of the wood,…) and how the internal forces are distributed into the joint to finally figure out how to design the traditional carpentry connections. The present paper aims to raise those questions focusing on the Single Step Joint design. Even if this common joint between the rafter and the tie beam is geometrically simple, one may pick up three geometrical configurations of Simple Notched Joints from the past till today: the geometrical configuration ideal (GCID), the geometrical configuration perpendicular to the tie beam (GCPTB) and the geometrical configuration perpendicular to the rafter (GCPR). The first one is more recent because it requires a highest accuracy production, and so the use of the new technologies (e.g., CNC). For each one, some general design rules about the geometrical parameters of the Single Step Joint are defined by some European standards (Siem and Jorissen, 2015), but no one details how to design this connection to prevent shear cracks at the heel depth or the compressive crushing at the joint contact surfaces. Hence the design rules and the emergence of failure modes according to the geometrical parameters of the Simple Notched Joint must be defined. In order to check the design equations and the failure modes, lab tests about the three geometrical configurations of the Single Step Joint have been carried out, varying the heel depth, the shear length and the inclination of the rafter.